Modified minimally invasive surgical technique in human intrabony defects with or without regenerative materials—10‐year follow‐up of a randomized clinical trial: Tooth retention, periodontitis recurrence, and costs. (25th April 2022) - Cortellini, Pierpaolo; Cortellini, Simone; Bonaccini, Daniele; Tonetti, Maurizio S.
Abstract: Aim: The modified minimally invasive surgical technique (M‐MIST) optimizes wound stability in the treatment of intrabony defects. Short‐term observations show similar results as with flap alone or adjunctive regenerative materials. This study aims to compare the stability of the long‐term outcomes, complication‐free survival, and costs of the three treatment options. Materials and Methods: Forty‐five intrabony defects in 45 patients were randomized to M‐MIST alone ( N  = 15), combined with enamel matrix derivative (M‐MIST + EMD, N  = 15), or EMD plus bone‐mineral‐derived xenograph (M‐MIST + EMD + BMDX, N  = 15). Supportive periodontal care (SPC) and necessary re‐treatment were provided for 10 years. Results: Three subjects were lost to follow‐up. Clinical attachment level differences between 1 and 10 years were −0.1 ± 0.7 mm for M‐MIST, −0.1 ± 0.8 mm for M‐MIST + EMD, and −0.3 ± 0.6 mm for M‐MIST + EMD + BMDX ( p  > .05 for within‐ and between‐group differences). Four episodes of recurrence occurred in the M‐MIST group, four in the M‐MIST + EMD group, and five in the M‐MIST + EMD + BMDX group. No significant differences in complication‐free survival were observed between the three groups ( p  = .47). Complication‐free survival was 7.46 years (95% confidence interval: 7.05–7.87) for the whole population. The M‐MIST + EMD + BMDX group lost one treated tooth. Data indicated no significant inter‐group difference of the total cost of recurrence over 10 years. When the baseline cost of treatment was considered, the total cost was lower for M‐MIST alone. Conclusions: Teeth with deep pockets associated with intrabony defects can be successfully maintained over the long term with either M‐MIST alone or by adding a regenerative material in the context of a careful SPC programme. M‐MIST alone provided similar short‐ and long‐term benefits as regeneration, at a lower cost. These findings need to be confirmed in larger, independent studies.